The Dynamic Changes of Capillary Permeability and Upregulation of VEGF in Rats Following Radiation‐Induced Brain Injury. (February 2014) - Jin, Xuelong; Liang, Bin; Chen, Zequn; Liu, Xingju; Zhang, Zhiwen
Abstract Objective To explore the dynamic changes of capillary permeability and the expression of VEGF in cerebral cortex after RIBI. Methods Male SD rats were randomly divided into the RIBI group and control group, and the RIBI group was randomly subdivided into five groups for analysis on day 1, 3, 7, 14, and 28, respectively. We established an RIBI model, and then evaluated BBB permeability by EB. We also measured the expression of VEGF with IHC stain and western blot. Results EB extravasation in injured cortex of RIBI group was increased at five time points compared with the control group. The western blot results and IHC revealed that the levels of VEGF expression in the RIBI groups was significantly increased at day 1 compared with the control group, then rose to a maximum at day 7, and subsequently the levels of expression recovered from day 14 to 28. Conclusions The increases in both BBB permeability and VEGF expression in the brain cortex of RIBI groups at same time period confirmed the possibility of brain injury following irradiation of 6 Gy.